INTEGRASI PANTI SOSIAL, RUMAH SUSUN DAN BUDIDAYA JAMUR SEBAGAI SOLUSI ARSITEKTUR REGENERATIF KAMPUNG KUMUH DAN TUNAWISMA DI JAKARTA - Japoetro, Shevia Florentia; Carina, Nina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
The increasing number of homeless individuals and the emergence of informal settlements in Jakarta reflect the complex interconnection between social and environmental issues. Despite the government’s efforts to provide solutions through social shelters and low-cost rental housing (Rusunawa), many individuals continue to live in illegal and inadequate dwellings due to limited access to employment, skills training, and basic life-supporting facilities. Informal settlements not only highlight social vulnerability but also contribute to environmental degradation—particularly along riverbanks, which are often polluted and poorly managed. This study explores the potential to redevelop these settlements into creative vertical housing and social shelters that not only provide decent living spaces but also integrate economic empowerment and ecological regeneration through the incorporation of a mushroom cultivation center. Mushrooms were selected for several reasons: they are commonly found in humid environments such as informal settlements, they are a widely favored food source, and they are well-suited to urban areas with limited space. Moreover, mushrooms have economic value and support organic waste processing systems. The specific mushroom types used in the project—straw mushrooms, oyster mushrooms, reishi, and eucalyptus mushrooms—were chosen based on site conditions, user needs, and the limited human resources available among future residents. The methodology includes literature review, precedent studies, and analysis of site conditions and the socio-ecological needs of users. The design process follows four key stages: (1) identifying the needs of marginalized communities in informal areas, (2) analyzing the potential of mushrooms as social and ecological agents, (3) integrating regenerative functions into the spatial program, and (4) formulating a creative housing concept rooted in regenerative, educational, and recreational architecture. Through this study, it becomes evident that regenerative architecture offers a promising approach to addressing homelessness by integrating it with mushroom cultivation systems. Beyond serving as a food and waste solution, mushroom cultivation presents broader opportunities for empowering homeless communities and improving local ecosystems. The outcomes of this study provide a conceptual foundation and design reference for developing socio-ecological-architectural programs as effective solutions for ensuring sustainability in Jakarta’s marginal urban areas. Keywords: homeless; jakarta; mushroom; regenerative; social housing Abstrak Fenomena meningkatnya jumlah tunawisma dan munculnya permukiman kumuh di Jakarta mencerminkan kompleksitas permasalahan sosial dan lingkungan yang saling berkaitan. Meski pemerintah telah mengupayakan solusi melalui panti sosial maupun penyediaan rumah susun sederhana sewa (rusunawa), banyak individu tetap tinggal di hunian ilegal dan tidak layak karena keterbatasan akses pekerjaan, keterampilan, dan fasilitas pendukung kehidupan. Permukiman kumuh tidak hanya memperlihatkan sisi kerentanan sosial, tetapi juga memperburuk kualitas lingkungan, terutama di area bantaran sungai yang rawan tercemar dan tidak tertata. Studi ini menyoroti potensi pengembangan ulang kawasan kumuh menjadi rusun dan panti sosial kreatif yang tidak hanya menyediakan hunian layak, tetapi juga fungsi pemberdayaan ekonomi dan regenerasi ekologis melalui integrasi pusat budidaya jamur. Budidaya jamur dipilih karena jamur beberapa alasan seperti jamur dapat dijumpai setiap hari khususnya pada Kawasan lembab seperti permukiman kumuh; jamur merupakansalah satu bahan makanan yang disukai dan cocok diterapkan di area perkotaan dengan lahan terbatas, bernilai ekonomi, serta mendukung sistem pengolahan limbah organik. Jenis jamur yang digunakan secara spesifik adalah jamur merang, jamur tiram, jamur reishi dan jamur kayu putih berdasarkan kriteria konteks tapak dan kebutuhan serta batasan sumber daya manusia yang akan menghuni proyek. Metode yang digunakan meliputi studi literatur, studi preseden, serta analisis tapak dan kebutuhan sosial-ekologis pengguna. Proses pengumpulan data analisis dan hasil jurnal dilakukan melalui empat tahap: (1) identifikasi kebutuhan masyarakat marjinal di kawasan kumuh, (2) kajian potensi jamur sebagai agen sosial dan ekologis, (3) integrasi fungsi regeneratif ke dalam program ruang, dan (4) penyusunan konsep rusun kreatif berbasis arsitektur regeneratif, edukatif, dan rekreatif. Melalui kajian tersebut akan ditemukan bahwa solusi regeneratif arsitektur dapat membantu menyelesaikan permasalahan tunawisma yang diintegtrasikan dengan pusat mengembangan jamur. Budidaya jamur tidak hanya dapat mengatasi limbah dan sumber pangan tetapi dapat memberikan potensi besar bagi tunawisma dan ekosistem secara luas. Hasil kajian dapat inspirasi serta dasar pemikiran untuk mengembangkan program ruang sosial-ekologis-arsitektural sebagai solusi efektif demi keberlanjutan ekosistem di kawasan urban marjinal Jakarta.